IMPLEMENTATION OF BINARY SEARCH TREE METHOD FOR ANDROID-BASED MORSE CODE DESCRIPTION - Nurul Chafid; Apriyanto Saputra (Jurnal Ilmiah Universitas Satya Negara Indonesia, 2024)
Morse code is a code that is still used by ORARI and the Scout in communicating. LearnMorse code requires an understanding of the cues delivered because Morse code was notsubmitted as a visualization of dots and lines, but must understand the long and shortsignal of Morse code. Morse tree method is used to facilitate the deciphering Morse codemessage. The aim of this study is to apply the method in a binary search tree andimplements Morse on android platform in the form of short messages using Morse code.Methods of approach and the development of systems using object-oriented approachand waterfall method. Results from this study that to change or alter the text to Morsebe required text identification numbers used to trace the Morse tree with a binary searchtree method. The application of Morse code signaling carried out in the interval of 200milliseconds for every point. Binary tree search method can be applied in tracing theMorse tree and implemented on the android platform for deploying long and short signalMorse code.